Current use of noninvasive prenatal testing in Europe, Australia and the USA: A graphical presentation. (3rd April 2020) - Gadsbøll, Kasper; Petersen, Olav B.; Gatinois, Vincent; Strange, Heather; Jacobsson, Bo; Wapner, Ronald; Vermeesch, Joris R.; ,; Vogel, Ida
Abstract: Introduction: Noninvasive prenatal testing (NIPT) using cell‐free fetal DNA has increasingly been adopted as a screening tool for fetal aneuploidies. Several studies have discussed benefits and limitations of NIPT compared with both ultrasound and invasive procedures, but in spite of some shortcomings NIPT has become extensively used within the last 5 years. This study aims to describe the current use of NIPT in Europe, Australia and the USA. Material and methods: We conducted a survey to describe the current use of NIPT. Colleagues filled in a simple email‐based questionnaire on NIPT in their own country, providing information on (a) access to NIPT, (b) NIPT's chromosomal coverage, (c) financial coverage of NIPT for the patient and (d) the proportion of women using NIPT in pregnancy. Some data are best clinical estimates, due to a lack of national data. Results: In Europe, 14 countries have adopted NIPT into a national policy/program. Two countries (Belgium and the Netherlands) offer NIPT for all pregnant women, whereas most other European countries have implemented NIPT as an offer for higher risk women after first trimester screening. In Australia, either combined first trimester screening (cFTS) or NIPT is used as a primary prenatal screening test. In the USA, there are no national consensus policies on the use of NIPT; however, NIPT is widely implemented. In most European countries offering NIPT, the proportion of women using NIPT is well below 25%. In the Netherlands, Austria, Italy, Spain and most Australian and American States, 25%‐50% of women have NIPT performed and in Belgium testing is above 75%. In most countries, NIPT reports on trisomy 13, 18 and 21, and often also on sex chromosome aneuploidies. Only in Belgium, the Netherlands, Lithuania, Greece, Cyprus and Italy is NIPT offered predominantly as a genome‐wide test (including some microdeletions or a whole genome coverage). Conclusions: Noninvasive prenatal testing has been widely adopted throughout Europe, Australia and the USA, but only a few countries/states have a national policy on the use of NIPT. The variation in NIPT utilization is considerable.